Selection parameters of a new “coerulea” multiflora hybrid: Cattlianthe aurora’s blue pride - Machado Neto,Nelson Barbosa (2019)
Abstract Cattlianthe Aurora’s Blue Pride is a new hybrid with lavender-blue flower, higher floral count than Cattleya Memoria Jack Hayden and larger than Cattlianthe Portia Baronesa. For the first time, a floral trait is being used in a documented scientific approach to help in the selection of superior plants in a population.